MILA: Low-cost BCI framework for acquiring EEG data with IoT - Rolly Maulana Awangga; Syafrial Fachri Pane; Dzikri Ahmad Ghifari; Tri Angga Dio Simamora; Mochamad Yusuf Asyhari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The brain is a vital organ in the human body that acts as the center of the human nervous system. Brain-computer interface (BCI) uses electroencephalography (EEG) signals as information on brain activity. Hospitals usually use EEG as a diagnosis of brain disease. Combining EEG as part of IoT (Internet of Things) with high mobility is challenging research. This research tries to make a low-cost BCI framework for motorcycle riders. Analysis of brain activity from EEG data when motorcycle riders turn left or turn right. Therefore, the method of further installation must produce the right features to obtain precise and accurate brainwave characteristics from EEG signals. This research uses the concept of IoT with software engineering to recording human brain waves so that it becomes a practical device for the wearer. The purpose of this study is to create a low-cost BCI framework for obtaining EEG data.